2015
DOI: 10.1002/polb.23806
|View full text |Cite
|
Sign up to set email alerts
|

Coatings with thermally switchable surface energy produced from poly(ethylene oxide)‐poly(dimethylsiloxane) block copolymer films

Abstract: This work explores coatings with thermally switchable wetting behavior, based on block copolymers that possess both hydrophilic and hydrophobic segments. The amphiphilic block copolymers were synthesized by coupling allyl‐ended poly(ethylene oxide) (PEO) and hydride‐ended poly(dimethylsiloxane) (PDMS) oligomers via a Pt catalyst. One near‐symmetric diblock possessed an order‐disorder transition temperature (TODT) of 64 °C. When cooled through TODT in ambient air, the PDMS domains wet the film's surface, produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…This appears to be related to the diffusion and rearrangement of the PS- b -PEO when heated (60 ℃). This in agreement with the findings of Davis and Register (2015), who reported that BCP had the ability to alter physical conformation in response to local environmental conditions, including temperature and pH and upon dramatic switchable properties which are dependent upon chain length (molecular weight), composition and architecture. The increased number of Ag precursor coatings increased the area of LDPE films covered with antimicrobial Ag + compared to those films receiving a lower number of Ag coating applications (see Table 1), thus, increased antimicrobial activity against all test microorganisms was observed.…”
Section: Characterisation Of Ag-coated Ldpe Filmssupporting
confidence: 92%
“…This appears to be related to the diffusion and rearrangement of the PS- b -PEO when heated (60 ℃). This in agreement with the findings of Davis and Register (2015), who reported that BCP had the ability to alter physical conformation in response to local environmental conditions, including temperature and pH and upon dramatic switchable properties which are dependent upon chain length (molecular weight), composition and architecture. The increased number of Ag precursor coatings increased the area of LDPE films covered with antimicrobial Ag + compared to those films receiving a lower number of Ag coating applications (see Table 1), thus, increased antimicrobial activity against all test microorganisms was observed.…”
Section: Characterisation Of Ag-coated Ldpe Filmssupporting
confidence: 92%